Nozick’s Proviso: Misunderstood and Misappropriated - Wündisch, Joachim; Justus Liebig University Giessen (My University, 2013)
After almost forty years, Robert Nozick's seminal right-libertarian classic Anarchy, State, and Utopia continues to stand at the center of much of the discussion regarding property and its initial acquisition. Nozick's most important contribution to that discussion is the formulation of his entitlement theory. Although the theory has received nearly unparalleled attention, its interpreters have misunderstood and misappropriated its most essential part: Nozick's proviso. This paper presents a brief selection of the most representative interpretations of Nozick's proviso, criticizes them, offers a textually well founded alternative reading of the proviso, and discusses its implications for Nozick's entitlement theory as well as right-libertarian theories of property more generally.
Keywords: Robert Nozick; Entitlement Theory; Principle of Justice in Acquisition; Lockean Proviso; New Baseline Interpretation; ddc:100; ddc:330